Cationic iridium complexes with an alkyl-linked bulky group at the cyclometalating ligand: synthesis, characterization, and suppression of phosphorescence concentration-quenching. (4th August 2021) - Song, Yongjun; Ren, Hao; Meng, Xianwen; He, Lei
Abstract : Cationic iridium complexes with a bulky 2, 2-diphenylethyl group at the cyclometalating ligand show remarkably suppressed phosphorescence concentration-quenching. Abstract : Suppression of phosphorescence concentration-quenching is critically important for the application of phosphorescent iridium complexes in various fields. Two cationic iridium complexes with suppressed phosphorescence concentration-quenching, namely [Ir(dpeppy)2 (bpy)]PF6 (1 ) and [Ir(dpeppy)2 (phpzpy)]PF6 (2 ), have been designed and synthesized by using 2-(4-(2, 2-diphenylethyl)phenyl)pyridine (dpeppy) as the cyclometalating (C^N) ligand, and 2, 2′-bipyridine (bpy) and 2-(1-phenyl-1 H -pyrazol-3-yl)pyridine (phpzpy) as the ancillary ligands. The bulky 2, 2-diphenylethyl group in dpeppy is linked to the cyclometalated 2-phenylpyridine moiety through a short alkyl chain, which provides large steric hindrance to the complexes without largely disturbing the emission properties of the emissive iridium-complex cores. In solution and thin films, complexes 1 and 2 exhibit orange-red and blue-green emission, respectively, which resembles that from the parent complexes without an alkyl-linked bulky group at the C^N ligand. In neat films, complexes 1 and 2 afford much higher phosphorescence efficiencies than the parent complexes, because the 2, 2-diphenylethyl group remarkably suppresses the phosphorescence concentration-quenching. Solid-state light-emitting electrochemical cells (LECs) using complex 2 as the emitting material afford green electroluminescence with a peak external quantum efficiency of 5.6%, which is much more efficient than the LECs based on the parent complexes. It is shown that attaching bulky groups at the C^N ligand through a short alkyl chain is an effective way to suppress the phosphorescence concentration-quenching of cationic iridium complexes without largely altering the emission properties of the iridium-complex cores.